BARE ICE FIELDS DEVELOPED IN THE INLAND PART OF ANTARCTICA - タカハシ, シュウヘイ; エンドウ, タツオ; アズマ, ノブヒコ; メシダ, シゲミ; TAKAHASHI, Shuhei; ENDOH, Tatsuo; AZUMA, Nobuhiko; MESHIDA, Shigemi (National Institute of Polar Research, 1992)
P(論文) Observations of a bare ice field was carried out at Seal Rock in the S∅r Rondane area, East Antarctica. A large sublimation rate, 200 to 280mm/a, was observed on the bare ice field. Air temperature on the bare ice was about 1℃ higher than that on snow surface. The large sublimation rate was explained from the low albedo of bare ice; its value was roughly estimated from heat budget considerations. The bare ice fields were classified into 4 types according to origin. departmental bulletin paper